Mercury distribution in continental shelf sediments from two offshore oil fields in southeastern Brazil - Lacerda, Luiz Drude de (2004)
Antropogenic enviromental impacts on marine areas are limited to protected costal sites such as bous and estuaries, or semi-enclosed seas. [...]